Impacto da radiação ionizante na consolidação de fraturas e efetividade do centrifugado de líquido amniótico humano como fator contribuinte para a cicatrização do tecido ósseo irradiado - Cláudio Beling Gonçalves Soares (2019)
THE IMPACT OF RADIATION ON THE HEALING OF FRACTURES AND THE EFFECTIVENESS OF CENTRIFUGATED HUMAN AMNIOTIC FLUID ON THE HEALING OF IRRADIATED BONE TISSUE. Radiotherapy is a very important therapeutic tool for the cancer treatment. However, it presents complications of difficult resolution, among them the pathological fracture. Systematically reviewing the scientific literature on pathological fractures after radiotherapy, the authors identified only poor quality publications. The reasons why it happens and which are the best methods for treatment are not clear in scientific literature. On the other hand, it is defined as having the potential for serious complications and poor results. In this research, we performed an experimental investigation using female rats, dividing them into three groups, with the objective of evaluating the real impact of radiation on the healing of femoral fractures and the effectiveness of acellular human amniotic fluid as an adjuvant factor in the healing of the irradiated bone tissue. A specific and efficient experimental model was developed to reproduce the effect of exposure to ionizing radiation on bone tissue healing. The first group (Positive Control) consists of animals exposed to radiation, receiving saline solution in the fracture focus. In the second (Study) the animals were irradiated and received human amniotic fluid at the fracture site. The third (Negative Control), which is the control group, was not exposed to radiation and received saline solution. The animals were evaluated usind radiografic exams and immunofluorescence. CD34, Ki-67, and interleukins 1 and 6 markers were evaluated by confocal microscopy to evaluate the neo-angiogenesis, fibroplasia and inflammatory response, respectively. The results allowed us to conclude that radiation interferes in the healing of femoral fractures in rats, making it less efficient, specially impacting cell proliferation and inflammatory activity in the fractured bone. There is no influence on neoangiogenesis. We also conclude that the acellular centrifugated human amniotic fluid is not a sufficient inducing factor for fracture healing in irradiated bones, to achieve the same efficiency as in bones not exposed to radiation. Keywords: RADIOTHERAPY. RADIATION EFFECTS. SPONTANEOUS FRACTURES. FRACTURE HEALING. AMNIOTIC FLUID.